Transport and survival of viruses in the subsurface-processes, experiments, and simulation models - Azadpour-Keeley, Ann; Ward, C. Herb (Remediation (New York, N.Y.), 2005)
The remediation of groundwater contaminated with waterborne pathogens, in particular with viruses, is based on their probable or actual ability to be transported from the source of origin to a point of withdrawal while maintaining the capacity to cause infections. The transport is often associated with both the unsaturated and saturated subsurface composed of varying geological settings with commensurate hydrogeological variability. Included among the most important hydrogeological factors that can be used to evaluate viral transport are the flux of moisture in the unsaturated zone, the media through which the particles travel, the length of the flow path, and the time of travel. With respect to the movement and inactivation of viruses in the subsurface, the vadose zone can provide an effective barrier for movement into groundwater and for the protection of downgradient points of withdrawal and use. Models developed to predicate viral transport in soil and groundwater are introduced, including screening models and more sophisticated predictive numerical models. As evidenced by the exponential growth of virus transport research in the literature, as well as a continuing interest in human health, the subject will continue to be one of critical importance to professionals active in the development, treatment, and conveyance of groundwater in the future. © 2005 Wiley Periodicals, Inc.